Eco-friendly management of tomato late blight using botanicals, bio-control agents, compost tea and copper fungicides - GOPI, R; AVASTHE, R K; KALITA, H; YADAV, A; DAS, S K; RAI, DINISHA (The Indian Journal of Agricultural Sciences, 2020)
Tomato is affected by the major disease late blight caused by Phytophthora infestans in Sikkim. In vitro experiment of biocontrol agents, botanicals and organically approved chemicals evaluated against P. infestans revealed that garlic, Trichoderma harzianum, copper oxychloride and copper hydroxide were effective. In field experiment conducted during 2014 and 2015, copper oxychloride @0.25% was found most effective followed by copper hydroxide @0.25% for the management of late blight. The pooled mean yield of tomato treated with copper oxychloride was recorded highest with 8.99 t/ha, 24.50 t/ha and 25.33 t/ha for open, rain shelter and tunnel, respectively followed by copper hydroxide. Hence, copper fungicides can be used for the management of late blight in tomato in organic farming.